2018
DOI: 10.32734/injar.v1i2.250
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value A Dried Fish Business Development in Bengkulu City

Abstract: The study aims to analyze the economic value of dried fish business by considering its added value of Hayami and marketing. This study uses primary data by surveying 55 dried fish producers in Bengkulu city. The results show that the average output price of dried fish is Rp6,586.61/kg. Using formula of Hayami’s added value, the average added value gained is Rp3,486.14/kg. This informs that every a kilogram of fresh fish processed into dried fish will create added value of Rp3,486.14. When labor under considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…These results were similar to the study by Madan et al [63] who found that costs were the key factors that influenced the income of dried fish processors in India. Sumantri et al [64] and Herawan et al [65] also found that the cost of raw materials affected the income of the fish-drying business in Indonesia. Besides the prices of raw materials, experience is also considered as one of the key factors that positively influence income [65].…”
Section: Discussionmentioning
confidence: 99%
“…These results were similar to the study by Madan et al [63] who found that costs were the key factors that influenced the income of dried fish processors in India. Sumantri et al [64] and Herawan et al [65] also found that the cost of raw materials affected the income of the fish-drying business in Indonesia. Besides the prices of raw materials, experience is also considered as one of the key factors that positively influence income [65].…”
Section: Discussionmentioning
confidence: 99%
“…Kualitas ikan asin dapat terganggu apabila produsen mengefisiensi penggunaan garam. Selain itu, Sumantri, et al (2018) juga menyoroti analisis nilai rantai produksi ekonomi pada usaha ikan kering di Bengkulu, dimana tercatat bahwa nilai bisnis semakin meningkat apabila biaya tenaga kerja ditambah.…”
Section: Deskripsi Bisnisunclassified